1986
DOI: 10.1159/000169445
|View full text |Cite
|
Sign up to set email alerts
|

Simple Assessment of the Efficacy of Peritoneal Transport in Continuous Ambulatory Peritoneal Dialysis Patients

Abstract: The efficacy of peritoneal transport was assessed in 13 permeability studies in 11 continuous ambulatory peritoneal dialysis (CAPD) patients. During each study the in situ intraperitoneal volume was measured as well as the dialysate and plasma concentrations of various solutes with a molecular weight range from 60 to 5,500. As clearance estimations are unsuitable for the purpose of permeability studies, mass transfer area coefficients were used. By applying a simple mathematical model assuming first-order kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 5 publications
0
42
1
Order By: Relevance
“…20 Figure 2. Univariate and multivariate Cox regression analyses, however, showed that PTP per se was not an independent predictor of mortality (multivariate hazard ratio, 1.10; 95% CI, 0.63 to 1.94; P=0.70) as shown in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Figure 2. Univariate and multivariate Cox regression analyses, however, showed that PTP per se was not an independent predictor of mortality (multivariate hazard ratio, 1.10; 95% CI, 0.63 to 1.94; P=0.70) as shown in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Dialysate-to-plasma ratios of creatinine at 4 hours was calculated after correction of glucose interference (19). Mass transfer area coefficient of creatinine normalized for body surface area was calculated by the formula described by Krediet et al (20). Dialysis adequacy, expressed as total weekly Kt/V, was determined by standard models (21).…”
Section: Peritoneal Equilibration Test and Dialysis Adequacymentioning
confidence: 99%
“…MTACcr was calculated using the simplified Garred equation based on the data obtained from PET test [22]: MTAC (ml/min) = (Vd/t) ln ({Vi · P} / {Vd [P - Dt]}), where Vd is the drained volume, t is the dwell time (240 min), Vi is the instilled dialysate volume, P is the plasma concentration, and Dt is the dialysate concentration at the end of dwell time, normally determined in the dialysate after drainage. The 4-hour ultrafiltration (4 h UF) during PET and 24-hour ultrafiltration of each patient were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Peritoneal transport characteristic was represented by dialysate-to-plasma ratios of creatinine at four hours (D/P4) and mass transfer area coefficients (MTAC) of creatinine as calculated by a formula previously described (25).…”
Section: Study Of Peritoneal Transportmentioning
confidence: 99%